Penggunaan gigitiruan sebagian lepasan kerangka logam pascaperawatan periodontal Using metal frame removable partial denture after periodontal treatment - Krisnadi Setiawan; Aprillia Adenan (DiscoverSys Inc., 2011)
Metal framework denture is needed in patient with tooth loss accompanied by the presence of periodontal disease inthe remaining tooth is needed. This denture primarily maintains the existing teeth post periodontal treatment. Theuse of metal framework in this case can help to prevent tooth movement and maintain tooth position afterperiodontal treatment. Therefore, the success of the treatment can be achieved because the metal characteristic ismore rigid when compared to other dental materials. This paper discusses the use of frame denture in patient afterperiodontal treatment on the remaining teeth in lower arch. It can be concluded that removable denture with metalframe combined with splint must be done on mobile teeth, to decrease mobile teeth and to preventincreasing of periodontal tissue damage after periodontal treatment.